2019
DOI: 10.3389/fnagi.2019.00033
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Plasma DPP4 Activity to BDNF Ratio and Mild Cognitive Impairment in Elderly Population With Normal Glucose Tolerance

Abstract: Objective: Since decreased brain-derived neurotrophic factor (BDNF) and increased dipeptidyl peptidase-4 (DPP4) activity have both been implicated in the pathogenesis of mild cognitive impairment (MCI), the aim of our study was to evaluate the association of MCI with plasma DPP4 activity to BDNF ratio (DBR) in an elderly population with normal glucose tolerance. Methods: We cross-sectionally measured C-reactive protein, interleukin-6, nitrotyrosine, 8-iso-PGF2a, DPP4 activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Although meta-analysis data showed a BDNF decrease in AD [199] and its concentration was associated with a reduction in hippocampal volume [200], other researchers believed that the possible biased use of plasma BDNF in MCI was critically risky [201]. [202] proposed the dipeptidyl peptidase-4 (DPP4) activity to BDNF ratio as a plasma biomarker. The Montreal Cognitive Assessment score decreased progressively when this ratio increased [203].…”
Section: And Alzheimer's Diseasementioning
confidence: 99%
“…Although meta-analysis data showed a BDNF decrease in AD [199] and its concentration was associated with a reduction in hippocampal volume [200], other researchers believed that the possible biased use of plasma BDNF in MCI was critically risky [201]. [202] proposed the dipeptidyl peptidase-4 (DPP4) activity to BDNF ratio as a plasma biomarker. The Montreal Cognitive Assessment score decreased progressively when this ratio increased [203].…”
Section: And Alzheimer's Diseasementioning
confidence: 99%
“…In consideration of the lack of significant differences in sociodemographic characteristics and laboratory parameters (including HbA1c levels and fasting blood glucose levels) between study groups, these results of the present study can be interpreted as indicating that the protective effects of DPP-4 inhibitors against cognitive impairment may be independent of their glucose-lowering effects. Although an inverse correlation between DPP-4 activity and BDNF levels was reported in the elderly population with normal glucose tolerance [ 24 ], to the best of our knowledge, our work is the first study demonstrating higher serum BDNF levels in patients using DPP-4 inhibitors when compared with patients using only metformin treatment.…”
Section: Discussionmentioning
confidence: 80%
“…In a study conducted on a total of 420 participants (208 patients with type 2 diabetes and 212 controls), in addition to the lower cognitive test scores, lower levels of BDNF (p<0.001) were reported in patients with type 2 diabetes when compared to controls [ 23 ]. Additionally, in another study conducted on the elderly population with normal glucose tolerance, it was shown that there was an inverse correlation between DDP-4 activity and BDNF levels (r=-0.456, p<0.001) [ 24 ]. In our study, there was a remarkable difference in serum BDNF levels between patients using DPP-4±metformin treatment and patients using only metformin treatment (394.51±205.66 ng/ml vs. 180.63±297.94 ng/ml; p=0.001).…”
Section: Discussionmentioning
confidence: 99%
“…In our meta-analysis, DPP4 inhibitors showed an improved effect on cognitive impairment in T2D, and DPP4i has previously been shown to have an improved effect on cognitive impairment [ 31 ]. Of course, broader cognitive tests are needed to support this idea.…”
Section: Discussionmentioning
confidence: 99%